Review of Nikos Christofis, ed., Erdoğan’s “New” Turkey: Attempted Coup D’état and the Acceleration of Political Crisis - Derisiotis, Anthony (Historein, 2022)
Review of Nikos Christofis, ed., Erdoğan’s “New” Turkey: Attempted Coup D’état and the Acceleration of Political Crisis. London: Routledge, 2020. xvi + 219 pp. To view the full text, click on the button "HTML".